Efficacy of ultrathin epidermal grafting followed by narrow band ultraviolet B therapy for stable vitiligo: a novel therapy - Kamcharla, Lakshmi; Tadi, Sahitya; Darla, Rakesh; Sidhabathuni, Nageswaramma (International Journal of Research in Dermatology, 2020)
Background: Different surgical techniques in the form of tissue or cellular grafting procedures are used alone or in combination with narrow band ultraviolet B (NBUVB) to treat stable vitiligo resistant to medical treatment. The aim of the study was to assess the cosmetic results obtained with combination therapy of ultrathin split-thickness skin grafts and adjuvant NBUVB therapy in resistant, stable vitiligo. Methods: Forty patients of stable vitiligo were treated with ultrathin split-thickness grafting and the patients were then put on NBUVB therapy. Extent of repigmentation and final cosmetic outcome at the recipient as well as donor sites were assessed. Results: The initial evidence of repigmentation was noted in the second week after starting NBUVB. Results showed 85% of patients had more than 90% repigmentation and the overall cosmetic results at the recipient site was good to excellent in 90% patients at the end of NBUVB treatment. Perigraft halo of depigmentation was seen in five patients (12%) on the recipient site. Hypertrophic scarring was seen in two patients at the donor site. Conclusions: Ultrathin split-thickness skin grafting, when combined with NBUVB therapy, leads to better cosmetic outcome with faster onset of repigmentation in resistant and stable vitiligo.